Energy expenditure estimate of subsoiling operation at varying depths - Machado, Thiago M.; Lancas, Kleber P. [UNESP]; Fiorese, Diego A.; Fernandes, Barbara B. [UNESP]; Testa, Joao V. P. [UNESP] (Univ Federal Campina Grande, 2015)
Soil decompression can be performed in several ways, the most common in the agricultural activities is the subsoiling. With the evolution of the embedded devices and electronics it is possible to vary the depth of the subsoiler and to perform decompression in an optimized way. The present study aimed to estimate the energy expenditure of a subsoiler operating in areas of different sizes and varying depths of subsoiling. A tractor 4x2 (FWA) and a subsoiler with five rods instrumented with equipment was used which enabled the analysis of hourly fuel consumption, operational fuel consumption, skating, average speed, effective field capacity, medium strength in traction and average power bar at the drawbar. From the results obtained in the field, were simulated in different electronic spreadsheets areas of different sizes with the subsoiler operating at fixed (PF) a variable depth (PV). It was found that the working time savings in PV in relation to PF ranged from 1.85 to 6.34%. A reduction in fuel consumption of 6.42 to 25.69% using PV in relation to PF was observed.
Keywords: subsoiler; fuel consumption; precision agriculture